Spontaneous esophageal rupture resulting in formation of multiple pulmonary artery pseudoaneurysms: A case report - Lena Becker, MD; Joshua Cornman-Homonoff, MD (Radiology Case Reports)
Esophageal rupture and pulmonary artery pseudoaneurysm are 2 rare but life-threatening conditions that are challenging to detect but require prompt intervention once diagnosed. The present case describes a patient with spontaneous esophageal rupture resulting in necrotizing pneumonia and multiple PAP that were ultimately managed via endovascular embolization combined with surgical resection. Although atypical, it emphasizes the need for a high degree of clinical suspicion when either of these diagnoses are on the differential and additionally illustrates another scenario in which interventional radiology and surgery can collaborate to optimize patient care.